Cyberbullying-Victimization Overlap Among Chinese University Students: Does Network Structure Matter? - Liu, Tzu-Hsuan (Crime & delinquency, 2022)
With widespread internet and social media use among youngsters, cyberbullying has emerged as a novel form of bullying. According to the routine activity and lifestyle theories, cyberbullying and victimization overlap significantly. However, the nature and mechanism of the overlap is not yet adequately understood. This study contributes to extant literature by investigating the role of network structure in cyberbullying-victimization overlap. Participants included 520 residential students from a single department of a Chinese university. This study applied prevalent, bivariate, and social network approach to investigate the overlap. Linear regressions with interactive terms are applied to investigate the moderating effect of network structure. First, the results revealed that the overlap phenomenon is robust against different approaches. Second, the findings demonstrated that indegree significantly moderates the effect of victimization on the perpetration of cyberbullying. Third, for betweenness and closeness, neither direct effect nor moderating effect, is statistically significant. Overall, cyberbullying-victimization overlaps among surveyed Chinese university students and social network may moderate the relationship between cyberbullying and victimization.